2018
DOI: 10.1016/j.smallrumres.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hair cortisone concentration as a novel tool to assess chronic stress in sheep with tick-borne fever

Abstract: A B S T R A C TTick-borne fever (TBF), caused by the bacterium Anaplasma phagocytophilum and transmitted by the tick Ixodes ricinus, has considerable consequences for animal welfare and economy in the sheep industry. Non-invasive, objective methods to quantify chronic stress are needed in order to evaluate the welfare impact of disease. The aim of this study was 1) to evaluate hair cortisol (HC) and hair cortisone (HCn) as biomarkers of chronic stress in sheep with TBF and 2) to test whether there was an assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…The absolute level in cortisol is comparable with previous studies ( 24 , 25 ). Age, in fact, is a factor that influences the levels of cortisol in the hair, as at the moment of birth or at a young age it is higher and decreases with the passage of time, something that is also observed in other farming species.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The absolute level in cortisol is comparable with previous studies ( 24 , 25 ). Age, in fact, is a factor that influences the levels of cortisol in the hair, as at the moment of birth or at a young age it is higher and decreases with the passage of time, something that is also observed in other farming species.…”
Section: Resultssupporting
confidence: 91%
“…We evaluated the production and welfare parameters of lambs from birth to slaughter. In contrast to saliva and blood cortisol, studies in other species have shown that hair cortisol is a proxy measure to the total retrospective activity of the HPA-axis over weeks or even months ( 24 , 25 , 31 ). Our data show clearly that the hair cortisol was less accumulated during the extensive breeding despite the various activities and experiences that the animals undergo, which affects this parameter (daily motor activity along high altitude slopes, sudden climatic changes, and presence of predators).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike plasma and saliva levels the fibre therefore provides a more stable measure of long term activation of the HPA axis. The finding of high levels of cortisone in the fibre is interesting and supportive of a previous observation of cortisone in wool (8,41). We speculate that the production of cortisone from cortisol by the enzyme 11βHSD2 takes place in the cells of the follicle bulb or, possibly, the root sheaths surrounding the growing fibre.…”
Section: Discussionsupporting
confidence: 90%
“…Within each system the comparison between the four-monthly times of the wool collection showed high levels of cortisol in the first month of life (T1) with a constant decrease in values over successive monthly periods of wool collection (T2, T3, and T4) in both systems (Figure 2[c]). These absolute levels of cortisol are comparable with previous studies (Stubsjøen et al 2015(Stubsjøen et al , 2018. Age, in fact, is a factor that influences the levels of cortisol in the hair, as at birth it is higher and decreases with the passage of time, something that is also observed in other farm animals.…”
Section: Chronic Cortisol Detectionsupporting
confidence: 90%